WATERFALL METHOD IN WEBSITE-BASED MOTORCYCLE RENT INFORMATION SYSTEM DESIGN AND SERVICES - Dicky Hariyanto; Ricki Sastra; Dany Ardyanto (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2022)
A lease is an agreement in which a payment is made for the temporary use of an item or property by another person. Berkah Bersama Motor is a business engaged in the service sector. However, in the data collection process at Berkah Bersama Motor, they still use manual processes such as recording customer personal data in books. In this research, the software development method used is the Waterfall method. Waterfall has the advantage that it can produce a fast and quality system so it was chosen in this study. The result of this web-based motorcycle rental management and service design program is that it can simplify the process of collecting customer personal data so as to reduce the risk of data loss because the storage media is still recorded in the book.